Making sense of construction improvement - Green, Stuart, 1958- (Chichester, West Sussex, UK ; Ames, Iowa : Wiley-Blackwell, 2011)
"The book sets out deliberately to challenge current directions in construction management, confronting the assumption that knowledge is uni-dimensional and accumulative. It will be argued that any understanding of construction management depends upon a critical orientation that does not subjugate understanding to performance. The book will initially set out the justification for adopting a critical perspective with reference to the broader literature on Construction Management Studies. Current trends in construction management will be set in the context of social, economic and political change over the past thirty years. A recurring theme throughout the book will be the complex interplay between the espoused managerial rhetoric and the realities of structural change in the construction sector. The discourse of construction management shapes, and is shaped by, the changing reality of the workplace. Linkages will also be made to the emergence of the enterprise culture and rhetoric of the global marketplace. Following the development of a critical perspective on construction management as a whole, specific chapters will be devoted to: business process re-engineering, lean construction, partnering, collaborative working, performance measurement and the assumed need for culture change"--
Machine generated contents note: Introduction; Construction management in critical perspective; Business process; re-engineering; Lean construction; Partnering; Collaborative working; Performance measurement; Culture change; Counter criticisms; Conclusion: where next?.
Machine generated contents note: Introduction; Construction management in critical perspective; Business process; re-engineering; Lean construction; Partnering; Collaborative working; Performance measurement; Culture change; Counter criticisms; Conclusion: where next?.
Includes bibliographical references and index.
Keywords: Construction industry -- Management; Economic history; Building -- Superintendence